Formal syntheses of (2R,3R)-3-hydroxy pipecolic acid and (2R,3S)-3-hydroxy pipecolic acid from L-ascorbic acid - Chavan, Subhash P.; Dumare, Nilesh B.; Pawar, Kailash P. (Tetrahedron Letters, 2015)
Formal syntheses of both cis and trans 3-hydroxy pipecolic acids is achieved from L-ascorbic acid. Present synthesis describes use of chiral pool approach in which epimerization, Staudinger reaction and Cyclization reactions were employed as key steps. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 3-Hydroxy pipecolic acid; cyclization; Epimerization; L-Ascorbic acid